Analisis Perbandingan Kinerja Alat Pengering Rumah Kaca Tipe Rotari Sistem Tertutup Dengan Sistem Semi Tertutup Terintegrasi Dengan Tungku Biomasa Menggunakan Penukar Kalor Dua Tingkat Untuk Mengeringkan Ikan Nila - hafizh, Taufiqul; yahya, M; Prima , Raihan D.; Bayu , Nebim (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
The aim of this research is to compare the performance of an open system rotary type greenhouse effect dryer (APERK-TR-STP) system 1 with a closed system (APERK-TR-SST) system 2 for drying tilapia fish. In the APERK-TR- system, 1 fish is dried from an initial weight of 90.56 kg (initial water content 69.08% wet basis (bb) to a final weight of 30.33 kg (final moisture content 20% bw) at an average temperature 56.38 oC with a mass air flow rate of 0.459 kg/s takes 12 hours. Meanwhile in the APERK-TR-SST system 2 tilapia fish are dried from an initial weight of 91.49 kg (initial water content 69.40% bw) up to final weight of 19.27 kg (final moisture content 20% bw) at an average temperature of 53.98 oC with an air mass flow rate of 0.459 kg/s required 12 hours